2019
DOI: 10.25159/1998-8125/5833
|View full text |Cite
|
Sign up to set email alerts
|

Online servicescape dimensions as predictors of website trust in the South African domestic airline industry

Abstract: Increased costs, competition and a dynamic environment have led to South African domestic airlines relying more on their own websites as outlets for airline tickets. Customers’ e-commerce uptake with respect to buying airline tickets online has been slow, attributed mostly to a lack of website trust. A well-designed online service scape has been identified as an important contributor to website trust by several authors, but not yet in this particular context or industry. This study investigates the extent to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
1
13
0
1
Order By: Relevance
“…This finding resembles Harris and Goode (2010), as they stated that aesthetic appeal has a positive and significant effect on Trust. Also, the research conducted by Kühn et al (2015), on the airline's website found that Aesthetic Appeal has a significant relationship with the Trust on the website.…”
Section: Discussion the Role Of Aesthetic Appeal On Trust In Websitementioning
confidence: 98%
See 2 more Smart Citations
“…This finding resembles Harris and Goode (2010), as they stated that aesthetic appeal has a positive and significant effect on Trust. Also, the research conducted by Kühn et al (2015), on the airline's website found that Aesthetic Appeal has a significant relationship with the Trust on the website.…”
Section: Discussion the Role Of Aesthetic Appeal On Trust In Websitementioning
confidence: 98%
“…This finding is similar to Harris and Goode (2010) because they stated that financial security has a positive and significant effect on customer trust in a website. Further, Kühn et al (2015), found on the airline's website that financial security also has a significant relationship with trust on its website.…”
Section: The Role Of Financial Security On Trust In Websitementioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the development of information technology and the growing number of website users, a lot of studies have transformed their focus from the physical environment (servicescape) to the online environment, which is used in different terms such as "e-escape (Koering, 2003)," "online servicescape (Harris & Goode, 2010;Kühn et al, 2019)," "virtual atmospherics (Abarbanel et al, 2015)," "digital servicescape (Ballantyne & Nilsson, 2017)," and "e-servicescape" (Hopkins et al, 2009;Lai et al, 2014;Lee & Jeong, 2012;Tankovic & Benazic, 2018;Teng et al, 2018;Wu et al, 2018).…”
Section: E-servicescapementioning
confidence: 99%
“…Many studies have applied the e-servicescape dimensions of Harris and Goode in different online contexts such as online shopping (Tankovic & Benazic, 2018;Wu et al, 2018), the hospitality and tourism sector (Huang et al, 2017), and the airline sector (Kühn et al, 2019).…”
Section: E-servicescapementioning
confidence: 99%